1988
DOI: 10.1182/blood.v71.4.997.bloodjournal714997
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte/macrophage colony-stimulating factor stimulates monocyte and tissue macrophage proliferation and enhances their responsiveness to macrophage colony-stimulating factor

Abstract: Granulocyte-macrophage colony-stimulating factor (GM-CSF) is a specific humoral growth factor that stimulates both neutrophilic granulocyte and macrophage production by bone marrow hematopoietic progenitor cells. GM-CSF also stimulates the proliferation and clonal growth of both tissue macrophages and blood monocytes. Although at low concentrations GM-CSF was unable to support the long-term growth of tissue macrophages, it greatly enhanced their responsiveness to macrophage CSF (M-CSF, or CSF-1). This effect w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

1990
1990
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 0 publications
1
16
1
Order By: Relevance
“…In this study, we extend these observations by demonstrating that not only L929-CM (M-CSF or CSF-1) but also GM-CSF, which bears no structural similarity to CSF-1, stimulates the proliferation of rat liver macrophages in uitro. These results are comparable to earlier reports on macrophages isolated from other sources: Alveolar macrophages (17, 361, peritoneal exudate macrophages (371, blood monocytes (19) and bone marrow-derived macrophages (19,22) have all been shown to proliferate in uitro on incubation with CSF-1 or GM-CSF. In contrast, IL-2, IL-3 and IL-6, which induce proliferation of macrophages or their precursors in bone marrow and various other organs, did not stimulate liver macrophage proliferation in uitro.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we extend these observations by demonstrating that not only L929-CM (M-CSF or CSF-1) but also GM-CSF, which bears no structural similarity to CSF-1, stimulates the proliferation of rat liver macrophages in uitro. These results are comparable to earlier reports on macrophages isolated from other sources: Alveolar macrophages (17, 361, peritoneal exudate macrophages (371, blood monocytes (19) and bone marrow-derived macrophages (19,22) have all been shown to proliferate in uitro on incubation with CSF-1 or GM-CSF. In contrast, IL-2, IL-3 and IL-6, which induce proliferation of macrophages or their precursors in bone marrow and various other organs, did not stimulate liver macrophage proliferation in uitro.…”
Section: Discussionsupporting
confidence: 91%
“…Like other cytokines, IL-6 has a variety of biological activities, such as induction of B cell differentiation, T cell activation, induction of acute phase proteins, reduction of the G0-residence time of hematopoietic stem cells, and so on (45). GM-CSF is a 23-kd glycoprotein known to be a hematopoietic growth factor required for the proliferation and survival of hematopoietic cells committed to granulocytic and macrophage cell lineages and of myeloid leukemic cells (5,7,24). At least a part of the hematopoietic activity of SCG shown in this study would be explainable by the effects of SCG on the levels of IL-6 and GM-CSF.…”
Section: Discussionmentioning
confidence: 99%
“…These studies, however, did not investigate the possibility that M-CSF may potentiate the activity of other cytokines to induce proliferation, maturation or activation. Carocciolo et al showed that small doses of GM-CSF in addition to M-CSF produced macrophagic colonies from human bone marrow progenitors [26], and in the murine system, investigators have shown that GM-CSF enhances the responsiveness of macrophages to M-CSF [27], and TNF-a acts synergistically with M-CSF to induce proliferation [28]. Further experiments are needed to determine if M-CSF requires the presence of additional cytokines, such as IL-3, IL-4, YIFN, TNF-a and/or GM-CSF, to induce proliferation or activation of human blood monocytes.…”
Section: Discussionmentioning
confidence: 99%